Safety and efficacy of acarbose in the treatment of diabetes in Chinese patients - He, Ke (Dove Medical Press, 2014)
Acarbose is an α-glucosidase inhibitor that is commonly used to control postprandial blood glucose. It functions as a competitive and reversible inhibitor of small intestinal brush border glucosidase, blocks the degradation of starch and sucrose, and delays the absorption of glucose and fructose in the alimentary tract. The starch content of a diet might alter the hypoglycemic effects of acarbose because of its mechanism of action. Chinese individuals consume a typical Eastern diet, which is characterized by a high intake of whole grains, legumes, vegetables, fruits, and fish. These dietary habits allow acarbose to be used extensively in the People’s Republic of China. Several Chinese-based studies have demonstrated that the use of acarbose as a monotherapy had similar effects on other anti-diabetes agents in decreasing glycosylated hemoglobin (HbA1c) and blood glucose levels, and acarbose in combination with other anti-diabetic drugs could further reduce blood glucose and decrease the mean amplitude of glycemic excursions. Importantly, acarbose is safe and well tolerated, with a low incidence of adverse effects. This article provides a comprehensive review of the safety and efficacy of acarbose for the treatment of diabetes in Chinese patients.